Persepsi Pemuda-Pemudi Lampung Sai Batin Terhadap Pergeseran Tradisi Sebambangan di Era Modern (Pekon Turgak Kabupaten Lampung Barat) - Jesi Devialita; Hermi Yanzi; Edi Siswanto; Berchah Pitoewas; Abdul Halim (CV. ITTC INDONESIA, 2026)
This study aims to analyze in-depth the perceptions of young men and women in Saibatin Lampung regarding the shift in the Sebambangan tradition in the modern era, particularly in the Turgak Village area of ​​West Lampung Regency. This study employed a qualitative approach with descriptive methods. Data collection was conducted through in-depth interviews, observation, and documentation involving informants from among the youth and local traditional leaders. The results indicate that most young men and women disagree with the practice of the Sebambangan tradition in the modern era. This is based on the perception that its current implementation often deviates from original customary rules, is prone to triggering social conflict between families, and is considered out of step with current developments, educational levels, and the economic rationality of today's youth. Nevertheless, a small number of informants still accept the tradition with the following conditions: its implementation must return to strict customary guidelines and prioritize communication to avoid harming any party. The Sebambangan tradition is undergoing a significant paradigm shift among young people. This phenomenon indicates the need for adaptation efforts and cultural dialogue to prevent the noble values ​​of custom and local identity from being completely eroded by the dynamics of modernization.